A New 3D Volume-Based Method for Assessing Composites Curing Depth. (2022) - Gummadi, S.; Roulet, J.-F.; Rocha, M.G.
Abstract : Purpose/Aim: Develop a new method to evaluate the curing depth of conventional and bulkfill composites based on the total volume of cure (VOC) and compare to the ISO 4049 depth of cure standard (DOC) with different mold diameters. Materials and Methods: A total of 100 samples were made from 2 bulkfill composites and 2 conventional resin-based composites, 25 samples for each material, with 5 samples per diameter of 10 mm, 8 mm, 6 mm, 4 mm, and 2 mm using stainless steel molds of 10 mm length. An individually designed 3D printed frame was attached to a metal plate using stainless steel screws in order to secure a fixed position of the molds in relation to the Valo cordless LED LCU which was clamped to the metal plate with an adjustable arm. ISO DOC was measured according to ISO 4049. Then the domed cylinders were scanned and the VOC% was measured in the Autodesk Meshmixer software using the STL files obtained from the scanned data using a E4D planmeca scanning device. Geomagic software was used for 3D comparison of curing profiles of 10 mm diameter samples. Two-way analysis of variance (ANOVA) and Tukeys test for pairwise comparison was used to analyze the data. A difference plot assembled in the geomagic software was used for 3D comparison of curing profiles Results: ISO 4049 method that measures the center of the specimen does not represent the full potential of the LCU. With a 10 mm ∅ window of the LCU, 10 mm, 8 mm and 6 mm molds give identical results for DOC and VOC%. The difference between the bulkfill and regular composites was significant (p<0.05); bulkfill DOC was between 1.9x (Filtek) and 2.4x (Tetric) higher than for the regular composites. DOC and VOC% are both negatively influenced by smaller mold diameter (p<0.05). The non-homogenous nature of the LCU did not influence the VOC% and DOC. The non-homogenous nature beam profile of the LCU unit had an influence on the 3D curing profiles of the specimen, which can be explained with the higher absorption of the violet light from the composite Conclusions: Most of contemporary LCUs have diameters of the light exiting window >4 mm. since there were significant differences in DOC between ∅ 6 mm and ∅ 4 mm molds. ISO 4049 under-represents the DOC. The influence on the LCUs curing profile on ∅ 6 mm molds should be investigated in the future. The experiment should be repeated with other LCUs than the one used in this study. Results for the ISO DOC and volume of cure percent (VOC %) for different mold diameter samples for 4 materials Filtek Bulkfill one(FBO), Tetric Powerfill(TPF), Filtek Supreme (FS), and Tetric Prime(TP).